Evaluation of an inpatient psychocardiological rehabilitation program in Austria: Psychosocial outcomes of a six-month cohort study - Martin Matzka; Reinhard Lenz; Cathrin Köller-Janauschek; Maria Neubauer; Monika Mustak-Blagusz; Johann Mikl (PLoS ONE, 2025)
Background Resources for psychosocial care in conventional cardiologic settings are limited. To address this gap, the first inpatient psychocardiological rehabilitation program in Austria aimed at providing integrative rehabilitation for patients with concurrent heart and mental health conditions has been piloted. The six-week program is provided in two consecutive rehabilitation modules and focuses on psychological and psychotherapeutic interventions embedded within the key elements of conventional cardiac rehabilitation. The objective of this cohort study was to evaluate the psychosocial outcomes of the pilot program, with a particular emphasis on longer-term results. Methods This study is a quantitative observational outcome evaluation based on patient-reported data collected at four consecutive time points during and six months after completing the two-part program. We conducted a repeated measures multivariate analysis of variance (MANOVA) with heart-focused anxiety (CAQ), global psychological distress (SCL-90®-S) and health-related quality of life (SF-12) as combined dependent variables. Time and social functioning (SAS-SR) on admission were included as explanatory variables. Ninety patients provided informed consent, finished the program and provided follow-up data. Results Six months after rehabilitation, significant reductions were observed in patients’ heart-focused anxiety (ηp2 =.144) and global psychological distress (ηp2 =.057) as well as a significant increase in mental quality of life (ηp2 =.137) compared to the admission values. Effect sizes expectedly decreased over time. Physical quality of life remained relatively constant over time and was the only outcome for which social integration on admission was not a significant prognostic factor. Conclusions The results indicate sustainable reductions in psychosocial symptoms and improvements in health-related quality of life following the inpatient psychocardiological rehabilitation program in Austria. Targeted referral of patients to psychocardiological rehabilitation, individualized bio-psycho-social treatment plans and the provision of need-based, integrated aftercare are essential for achieving and sustaining optimal rehabilitation outcomes.